Genetics, society, and clinical practice - Harper, Peter S; Clarke, Angus (Bios Scientific Publishers, 1997)
This volume examines, from both ethical and clinical perspectives, the impact of increasing genetic knowledge on individuals and families. The authors use their experience of working within clinical genetics to describe the social implications arising from the ability to test for an increasing number of genetic diseases. Current controversial issues are described. Several chapters are based on lead articles and editorials the authors have been asked to write for \"The Lancet\" and the \"British Medical Journal\". The book provides an introduction to the effects on individuals of the practical issues associated with genetic testing and should, therefore, be of interest to all those involved in clinical genetics.
Keywords: Spojené království; dítě; Age of Onset; genetika, lékařská genetika; China; Ethics, Medical; Decision Making; věk při počátku nemoci; etika, bioetika, lékařská etika; Čína; Confidentiality; Reproductive Techniques, Assisted; asistovaná reprodukce; lékařská etika; Delivery of Health Care; lékařská genetika; Genetics, Medical; Child; genetické nemoci vrozené; potrat eugenický; Abortion, Eugenic; United Kingdom; důvěrnost informací; rozhodování; reprodukční lékařství; genetické služby; poskytování zdravotní péče; Genetic Diseases, Inborn; Genetic Services